HUMAN NATURE IN THE VIEW OF THE PHILOSOPHER AL-GHAZALI - Sukrina, Alfi; Aprison, Wedra (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2024)
This article aims to explain the views of the philosopher Al-Ghazali regarding human nature. Basically humans are born in a state of nature, it's just that as humans grow from infancy, toddlerhood, children to old age. So sometimes they show behavior that is out of their nature. So in this case it is necessary to know what human nature is, which in this article will outline the views of the philosopher Al-Ghazali regarding human nature. In terms of this library research, researchers take from trusted sources such as books, journal articles and documents that discuss human nature in the views of the philosopher Al-Ghazali. In collecting data, the author collected journals or articles that discussed human nature in the views of the philosopher Al-Ghazali. In this research the author uses a descriptive approach which describes human nature in the view of the philosopher Al-Ghazali. By taking action to analyze the data found. The findings in this article: (1) Biography of Imam Al-Ghazali (2) Works of Imam Al-Ghazali; (3) Human Nature in the View of Imam Al-Ghazali